Effects of V additions on the mechanical behavior of Au thin films for MEMS contact switches - T. Bannuru (2018)
Au, Au-V solid solution, and Au-V2O5dispersion films were fabricated for comparison of electrical and mechanical characteristics. Resistivity and nanoindentation hardness increased with increasing V content in all films, but the ratio of resistivity increase to hardness increase was much lower for the Au-V2O5films. Measurements of contact force and electrical contact resistance between pairs of Au or Au-V films show that increased hardness and resistivity in the alloy films results in higher contact resistance and less adhesion than in pure Au. These results imply that the Au-V2O5films may exhibit attractive behavior when used in a contact configuration, but this has not yet been tested.